Long noncoding RNA‐GAS5 attenuates progression of glioma by eliminating microRNA‐10b and Sirtuin 1 in U251 and A172 cells. (30th December 2019) - Ding, Yingjie; Wang, Jing; Zhang, Hongliang; Li, Huanting
Abstract: Long noncoding RNA (lncRNA) growth arrest‐specific 5 (GAS5) is implicated in several cancers via modulating microRNAs (miRs). However, little information is available about the correlation between GAS5 and miR‐10b. Therefore, we sought out to investigate the biological role of GAS5‐miR‐10b node mainly in glioma cells. We artificially modulated GAS5 to explore its roles in viability assayed by cell counting kit‐8 (CCK‐8), motile activities by 24‐Transwell assay, as well as apoptosis by a flow cytometer and Western blot assay. miR‐10b and Sirtuin 1 (Sirt1) were quantified by qRT‐PCR. After co‐transfection, we analyzed the viability, migration, invasion, apoptosis, and Sirt1 expression. Western blot was implemented to detect the phosphorylated forms of PTEN, PI3K, AKT, MEK, and ERK. GAS5 inhibited proliferation and motile behaviors, and fortified apoptosis. As for the viability and motile activities, the property of GAS5 was reversed in miR‐10b‐replenished U251 and A172 cells, while maintained in miR‐10b‐deficient cells. Additionally, GAS5‐induced apoptosis was abolished by miR‐10b overexpression while fortified by miR‐10b silence. Besides, GAS5 negatively modulated Sirt1 via miR‐10b. Moreover, Sirt1 negatively modulated PTEN and positively mediated the abovementioned regulators. GAS5 represses the process of glioma cells by decreasing miR‐10b, which as accompanied by Sirt1 silence‐induced inactivation of PTEN/PI3K/AKT and MEK/ERK cascades.